2019
DOI: 10.3389/fenvs.2019.00117
|View full text |Cite|
|
Sign up to set email alerts
|

Stormwater Ponds in the Southeastern U.S. Coastal Plain: Hydrogeology, Contaminant Fate, and the Need for a Social-Ecological Framework

Abstract: In lowland coastal regions of the southeastern United States, stormwater ponds are being built as the "green infrastructure" best management practice of choice for addressing the hydrologic changes associated with rapid urban and suburban development. In addition to dampening storm flows, stormwater ponds may provide pollution control and other ecosystem services. However, ponds are not native to this landscape. This review summarizes what is known about the effectiveness of these engineered ponds, which take … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…This same bloom posed a minimal to moderate threat to recreation (swimming, fishing; WHO 1999), categorized as minimal (< 10 μ g microcystins L −1 , typically < 20,000 cells mL −1 ), moderate (10–20 μ g microcystins L −1 , typically 20,000–100,000 cells mL −1 ), and high (> 20 μ g microcystins L −1 , typically > 100,000 cells mL −1 ) (USEPA document 820R15100). In addition to lakes and drinking water supplies, stormwater ponds (SWPs), constructed systems that mitigate flooding, often harbor cyanoHABs, including Microcystis blooms (Lewitus et al 2003; Siegel et al 2011; Greenfield et al 2017), because they accumulate nutrients (from fertilizers, pet waste, and others) from runoff, have low flow, and long residence times, which combined frequently lead to stagnation and eutrophication (Lewitus et al 2008; Serrano and DeLorenzo 2008; Beckingham et al 2019). SWPs are common in flood‐prone regions, for example, coastal South Carolina alone has > 21,000 SWPs, with many nestled within residential neighborhoods and golf courses (Lewitus et al 2003; Smith et al 2019).…”
Section: Figmentioning
confidence: 99%
“…This same bloom posed a minimal to moderate threat to recreation (swimming, fishing; WHO 1999), categorized as minimal (< 10 μ g microcystins L −1 , typically < 20,000 cells mL −1 ), moderate (10–20 μ g microcystins L −1 , typically 20,000–100,000 cells mL −1 ), and high (> 20 μ g microcystins L −1 , typically > 100,000 cells mL −1 ) (USEPA document 820R15100). In addition to lakes and drinking water supplies, stormwater ponds (SWPs), constructed systems that mitigate flooding, often harbor cyanoHABs, including Microcystis blooms (Lewitus et al 2003; Siegel et al 2011; Greenfield et al 2017), because they accumulate nutrients (from fertilizers, pet waste, and others) from runoff, have low flow, and long residence times, which combined frequently lead to stagnation and eutrophication (Lewitus et al 2008; Serrano and DeLorenzo 2008; Beckingham et al 2019). SWPs are common in flood‐prone regions, for example, coastal South Carolina alone has > 21,000 SWPs, with many nestled within residential neighborhoods and golf courses (Lewitus et al 2003; Smith et al 2019).…”
Section: Figmentioning
confidence: 99%
“…A large single pond will perform differently under identical conditions compared to multiple, in‐series ponds. This will ultimately impact the nitrogen and phosphorus cycle differently as sedimentation rates within the ponds highly impacted the amount of carbon and nitrogen sequestration via burial (Beckingham, Callahan, & Vulava, 2019). Ahilan et al (2019) utilized the Revitalized Flood Hydrographs rainfall model and the layer‐based hydro‐morphodynamic model to model suspended sedimentological effects.…”
Section: Constructed Stormwater Pondsmentioning
confidence: 99%
“…Gold et al [3] observed little to no improvement in downstream water quality and nutrient concentrations after watershed-scale implementation of wet stormwater ponds in an urbanizing coastal area. A growing number of researchers are recognizing that in-pond nutrient cycling may make urban stormwater ponds function as sources of dissolved nutrients [31,32], and there is a need for new research that investigates the mechanistic controls on nutrient cycling and downstream fate in these urban features of the built environment. We provide evidence here of the dynamic nature of in-pond DON and PON, and future studies should investigate this across temporal and spatial scales and in environments with varying ON sources such as with different types of vegetation.…”
Section: Plos Onementioning
confidence: 99%